Implementation strategies for providing optimised tuberculosis and diabetes integrated care in LMICs (POTENTIAL): protocol for a multiphase sequential and concurrent mixed-methods study - Najma Siddiqi; Catherine Hewitt; Zia Ul-Haq; Nauman Safdar; Kamran Siddiqi; Abdul Basit; Zohaib Khan; Steve Parrott; Razia Fatima; Saima Afaq; Zala Zala; Saima Aleem; et al. (BMJ Open)
Introduction Almost a quarter of patients with tuberculosis (TB) in Pakistan may also have diabetes, with an additional quarter in a pre-diabetic state. Diabetes is a risk factor for TB. When it co-occurs with TB, it leads to poorer outcomes for both conditions, considerably increasing the burden on individuals, families and the healthcare system. We aim to improve health, quality of life and economic outcomes for people with TB and diabetes by optimising diabetes prevention, screening and management within TB care. The objectives of this study are to: (1) design an integrated optimised tuberculosis-diabetes care package (Opt-TBD) and its implementation strategies; (2) pilot and refine these implementation strategies and (3) implement and evaluate the Opt-TBD care package in 15 TB care facilities in Pakistan.Methods and analysis We will work with the TB programme across two provinces of Pakistan: Khyber Pakhtunkhwa and Punjab. TB care facilities will be selected from urban and rural settings of these provinces and will include three levels: primary, secondary and tertiary care settings. This multiphase mixed-method study has three sequential phases. Once ready, the care package and its implementation strategies will be piloted to inform further refinement. The package will be implemented in 15 urban and rural TB care facilities and evaluated for its Reach, Effectiveness, Adoption, Implementation and Maintenance, and potential for scale-up. Quantitative data will assess provider adoption and the package’s accessibility and effectiveness for patients with TB and with diabetes and pre-diabetes. Qualitative data will explore barriers and facilitators for successful implementation and scale-up. Data will be analysed using statistical methods—including descriptive and inferential statistics—for quantitative data and framework analysis for qualitative data, with triangulation to integrate findings.Ethics and dissemination Ethics approval was granted by the National Bioethics Committee of Pakistan (NBCR-1010). Findings will be shared through academic publications, conferences and public outreach.